Dexmedetomidine protects from post-myocardial ischaemia reperfusion lung damage in diabetic rats - Gülay Kip; Ali Çelik; Mustafa Bilge; Metin Alkan; Hasan Ali Kiraz; Abdullah Özer; Volkan Şıvgın; Özlem Erdem; Mustafa Arslan; Mustafa Kavutçu (Libyan Journal of Medicine, 2015)
Objective: Diabetic complications and lipid peroxidation are known to have a close association. Lipid peroxidation commonly occurs at sites exposed to ischaemia, but distant organs and tissues also get damaged during ischaemia/reperfusion (I/R). Some of these targets are vital organs, such as the lung, liver, and kidney; the lung is the most frequently affected. The aim of our study was to investigate the effects of dexmedetomidine on I/R damage in lung tissue and on the oxidant/anti-oxidant system in diabetic rats. Material and methods: Diabetes was induced with streptozotocin (55 mg/kg) in 18 Wistar Albino rats, which were then randomly divided into three groups (diabetes control (DC), diabetes plus ischaemia-reperfusion (DIR), and diabetes plus dexmedetomidine-ischaemia/reperfusion (DIRD)) after the effects of diabetes were clearly evident. The rats underwent a left thoracotomy and then ischaemia was produced in the myocardium muscle by a left anterior descending artery ligation for 30 min in the DIR and DIRD groups. I/R was performed for 120 min. The DIRD group received a single intraperitoneal dose of dexmedetomidine (100 µg/kg); the DIR group received no dexmedetomidine. Group DC was evaluated as the diabetic control group and also included six rats (C group) in which diabetes was not induced. These mice underwent only left thoracotomy and were closed without undergoing myocardial ischaemia. Histopathological changes, activities of catalase (CAT) and glutathione-S-transferase anti-oxidant enzymes, and malondialdehyde (MDA) levels were evaluated in the lung tissues of all rats. Results: Neutrophil infiltration/aggregation was higher in the DIR group than in the C, DC, and DIRD groups (p=0.001, p=0.013, and p=0.042, respectively). The lung injury score was significantly higher in the DIR group than in the C and DC groups (p<0.0001 and p=0.024, respectively). The levels of MDA were significantly higher in the DIR group than in the C and DIRD groups. CAT activity was significantly higher in the DIR group than in the DIRD and C groups. Conclusion: Our results confirm that dexmedetomidine has protective effects against the lung damage resulting from I/R in diabetic rats. Future studies conducted to evaluate the effects of the use of dexmedetomidine on damage to various organs following different I/R durations may help understanding possible protective effects of dexmedetomidine and underlying mechanisms in tissue damage related to I/R injury.